On Thin Ice: Alcohol Promotion by Sport Resources - Belova, Yuliya (Journal of Economic Sociology, 2022)
Commercialization and the subsequent transformation of sports into an industry contributed to the increasingly conspicuous introduction of alcohol into the daily routine of athletes and fans. Under the current conditions, the partnership of sports organizations with the alcohol industry has become a legitimate phenomenon and has firmly rooted in the life of society, increasing social risks. At the same time, in public consciousness and scientific opinion, sport is still associated with health and constructive social behavior, but this value is increasingly being questioned. The authors of the peer-reviewed book Sport, Alcohol and Social Inquiry: A Global Cocktail (research in the sociology of sport) criticize the current situation and speak out against legislative easing for alcohol in sports to keep its true value. The monograph is an example of a sociological analysis of modern contradictions in the field of the promotion of alcoholic products by means of sports (at various levels of the sports hierarchy in an explicit or latent form). The authors demonstrate the clash of economic, political, and cultural aspects of the interaction between the state, the alcohol industry, fan groups, sports communities, and public health advocates based on protecting certain interests. The text presents vivid examples of the introduction of alcohol into the sphere of organizing sports (including big sports). The book covers a wide geography, representing a collection of cases on the “alcoholization of sports” in the United States, Brazil, Australia, France, Sweden, New Zealand and Japan.